Domestic-Foreign Research Characteristics and Hotspots of Marine Cities: Visualized Quantitative Research Based on CiteSpace - CHEN Shouxu; WANG Jianjun; DAI Xinzhao; LONG Nao; LIU Songling (Haiyang Kaifa yu guanli)
A visualized quantitative study based on the CiteSpace was carried out on 264 Chinese articles in the CNKI database and 3614 English articles in the Web of Science database from 1999 to 2023 with "marine city" as the theme word. The results show that the number of domestic and foreign marine city research literature is increasing in the fluctuation during the study period, and the mutation points coincide with the "13th Five-Year Plan for National Marine Economic Development", the establishment of the World Ocean Day and the entry into force of The Paris Agreement, respectively. The main affiliations for Chinese literature are universities located in regional leading marine cities, while the main affiliations for English literature are in Europe, America and China. The research hotspots at home and abroad have different focuses. The Chinese literature emphasizes on the research of "city" and pays more attention to the marine economy and industry in "marine city", while the English literature tends to focus on the research of "city" and "marine economy" in "marine city". The results of the English literature in "marine city" tend to favor the study of "ocean" and pay more attention to the management of marine environment and ecological evaluation. In a certain period of time in the future, emphasis should be placed on promoting the cross research between marine science and urban science, and strengthening the research and exploration of estuarine marine cities where salt and fresh water meet.